Institutional Delivery in the Philippines: Does a Minimum of 8 Antenatal Care Visits Matter? - Felly Philipus Senewe; Agung Dwi Laksono; Roy Glenn Albert Massie; Leny Latifah; Syarifah Nuraini; Rozana Ika Agustiya; Jane Kartika Propiana; Wahyu Pudji Nugraheni (Journal of Preventive Medicine and Public Health)
Objectives This cross-sectional study investigated the association between the utilization of 8 antenatal care (ANC) visits and delivery in a healthcare institution in the Philippines, using data from the 2022 National Demographic and Health Survey. Methods A sample of women who had given birth within the past 3 years was selected for analysis (n=4452). The association between ANC utilization and institutional delivery was assessed using logistic regression models, covariates by relevant socio-demographic factors, and childbirth history. Results We found that 97.2% of respondents who completed ANC opted for institutional delivery. A higher proportion of rural residents did not undergo institutional delivery than urban residents (12.9 vs. 6.9%). The group aged 20–24 years had the highest coverage (92.8%), and the group aged 40–44 years had the lowest. Higher education levels, employment, and greater wealth were associated with higher institutional delivery rates. Divorced or widowed mothers (85.1%) and grand multiparous mothers had lower rates than other groups. Multivariable logistic regression analysis showed a significant positive association between ANC utilization and institutional deliveries after adjusting for covariates (adjusted odds ratio, 2.486; 95% confidence interval, 2.485 to 2.487; p<0.001). Conclusions ANC visits were associated with deliveries in institutions in the Philippines. Policymakers should promote ANC by ensuring 8 World Health Organization-recommended visits, strengthening programs, conducting community outreach, addressing access barriers, and integrating maternal health services to increase institutional births and improve maternal and infant health.